Reproductive anxiety and fertility intentions: Gender differences in social mentality among university students - Xinwei Liao; Jing He; Chaoye Cao (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
Reproductive anxiety has emerged as an important concern among university students, shaping their perceptions of fertility, family formation, and future life planning. This study explored the gendered experiences of reproductive anxiety and its influence on fertility intentions among male and female university students. A qualitative research design was adopted, using semi-structured interviews with 30 students aged 18–25 years, equally divided by gender. Thematic analysis revealed that reproductive anxiety is strongly influenced by gender norms, socioeconomic uncertainty, family expectations, and changing social roles. Female students reported greater anxiety regarding the timing of motherhood, biological limitations, and the challenge of balancing education, career, and family responsibilities. Male students, while less vocal about fertility concerns, expressed anxiety mainly in relation to financial readiness and the social expectation of becoming future providers. The findings further showed that family pressure, cultural beliefs, and media portrayals intensify reproductive concerns, while these anxieties also contribute to stress, self-doubt, and uncertainty in long-term planning. The study concludes that reproductive anxiety is a multidimensional issue requiring greater academic, psychological, and policy attention. Universities should introduce gender-sensitive counseling and awareness programs to support students in navigating reproductive concerns and informed fertility decision-making.